2009
DOI: 10.4269/ajtmh.2009.81.140
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties in Maintaining Improved Handwashing Behavior, Karachi, Pakistan

Abstract: In an earlier study in Karachi, Pakistan, households that received free soap and handwashing promotion for 9 months reported 53% less diarrhea than controls. Eighteen months after the intervention ended, these households were enrolled in a follow-up study to assess sustainability of handwashing behavior. Upon re-enrollment, mothers in households originally assigned to the intervention were 1.5 times more likely to have a place with soap and water to wash hands (79% versus 53%, P = 0.001) and when asked to wash… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
86
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(93 citation statements)
references
References 20 publications
1
86
0
2
Order By: Relevance
“…We collected no objective data that verified whether handwashing frequency actually increased in intervention households, but, given the challenges in motivating and sustaining handwashing behavior, the use of hand towels as a behavioral cue merits further study. 5 The promotion and use of clean towels for hand drying could improve the effectiveness of handwashing because previous research suggests that, despite promotion of air-drying as a safe hand drying method, the behavior is often not practiced, most likely because it is time consuming and inconvenient. 6 More vigorous promotion of hand towels based on the results of this study would also require promotion of frequent (i.e., at least daily) towel washing and drying to prevent contamination and potential disease transmission.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We collected no objective data that verified whether handwashing frequency actually increased in intervention households, but, given the challenges in motivating and sustaining handwashing behavior, the use of hand towels as a behavioral cue merits further study. 5 The promotion and use of clean towels for hand drying could improve the effectiveness of handwashing because previous research suggests that, despite promotion of air-drying as a safe hand drying method, the behavior is often not practiced, most likely because it is time consuming and inconvenient. 6 More vigorous promotion of hand towels based on the results of this study would also require promotion of frequent (i.e., at least daily) towel washing and drying to prevent contamination and potential disease transmission.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 However, at least one study has documented the difficulty of sustaining handwashing behaviors and the attendant health impact. 5 Furthermore, a qualitative study of hand drying behavior in western Kenya suggested that, despite widespread messaging about the importance of using clean towels or air drying after handwashing, many people tended to use their pants or wraparound skirts for hand drying. 6 In response to the challenge of promoting and sustaining effective handwashing, innovative technologies for improving hand hygiene have been developed that consist of reusable hand towels with antimicrobial properties that are nontoxic and stable over time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Luby et al in their follow up in 2009 reported that sustainability of the project was limited. 21 They found that despite increased awareness of appropriate techniques of hand washing in the intervention areas; the hand washing behaviour was declined and purchasing soap for the purpose did not increase significantly. They concluded that it was the limitation of the project which didn't focused on increasing willingness and motivation to purchase and use soap.…”
Section: Intervention 2: Intensive Hand Washing Promotion On Childhoomentioning
confidence: 99%
“…They concluded that it was the limitation of the project which didn't focused on increasing willingness and motivation to purchase and use soap. 21 …”
Section: Intervention 2: Intensive Hand Washing Promotion On Childhoomentioning
confidence: 99%